1981
DOI: 10.1002/1097-4679(198107)37:3<681::aid-jclp2270370342>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Survey of professional education in ethics in clinical psychology intership programs

Abstract: Attempted to assess the extent to which clinical psychology internship programs offer professional education in ethical standards. While almost 80% of the programs offer such training, less than half of these provide a formal, systematic, and comprehensive learning experience. Many of the programs only provide a limited exposure to ethical standards that occurs on an informal basis as issues emerge in supervision. All but two of the programs that do not offer training in ethical standards reported that this wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…He found that formal training did produce significantly higher scores. Soon after, Newmark and Hutchins (1981) (Cripe, 1995;Golden & Kauperman, 1980;McCafferey, Malloy, & Brief, 1985). These studies have demonstrated that some neuropsychological teaching was occurring in most programs surveyed; however, training depth varied considerably, with few meeting standards developed by the International Neuropsychology Society (INS).…”
Section: What Interns Should Be and Are Taughtmentioning
confidence: 99%
“…He found that formal training did produce significantly higher scores. Soon after, Newmark and Hutchins (1981) (Cripe, 1995;Golden & Kauperman, 1980;McCafferey, Malloy, & Brief, 1985). These studies have demonstrated that some neuropsychological teaching was occurring in most programs surveyed; however, training depth varied considerably, with few meeting standards developed by the International Neuropsychology Society (INS).…”
Section: What Interns Should Be and Are Taughtmentioning
confidence: 99%
“…An internship requirement for doctoral programs and for later certification has become common in recent years. Newmark and Hutchins (1981) surveyed such programs. They found that although most offered some professional education in ethics, only about a third of the 185 programs provided a systematic, comprehensive learning experience.…”
Section: Code Development and Training In Ethicsmentioning
confidence: 99%
“…Such dissemination too would supplement the current methods of ethics and ethical decision-making training. Traditionally, of course, some graduate students of psychology obtain their dose of ethics through limited discussion of the various APA codes as part of a course on another topic or if in an applied field, through some practical discussion during an internship; undergraduates in psychology receive little or no discussion of ethics; postdoctoral graduates in psychology who apply for licensure obtain some preparation in ethics for the licensure exam (Newmark & Hutchins, 1981;Tymchuk et al, 1979). And after licensure or in areas of psychology where licensure is not required, there is limited interest in ethics (e.g., Tymchuk & Thompson, 1986).…”
Section: Systematic Discussion Of E T H I C a L Issuesmentioning
confidence: 99%